Advances in Cognitive Radio Systems - Cheng-Xiang Wang, Joseph Mitola III (IntechOpen, 2012)
Cognitive radio technologies are forms of wireless communication with many and varied applications. The contributions in this book will benefit researchers and engineers as they offer cutting-edge knowledge in the field. Subjects include uses of wideband voltage controlled oscillators, control planes for spectrum access and mobility in networks with heterogeneous frequency devices. Other chapters cover cognitive media access control and measurement methods for spectrum occupancy. In addition, there are contributions on delay analysis and channel selection in single-hop networks for delay-sensitive applications, the application of transmission security (TRANSEC) protocols to cognitive radio communication and the use of blind detection, parameters, estimation and the despreading of DS-CDMA signals in multirate, multiuser cognitive radio systems.